Cartera de crédito en la Cooperativa de Ahorro y Crédito “San Antonio”, agencia vinces en el periodo 2020-2021. - Miranda Pincay, Manuel De Jesús (2022)
The present case study that is going to be carried out in the “San Antonio” savings and credit cooperative of the city of Vinces, consists of the subjetc of credit portfolio in the period 2020-2021, the credit Portfolio is the most important and indispensable since it is income of any financial institution, especially for the savings and credit cooperative, the same ones that must promote collections offered to short, médium and long-term clients and as priority, find a way to recover credit portfolios, although the institution must implement a mechanism to know the member´s ability to pay in order to anticípate that in future terms they will not be able to cancel and. In turn, prevent an increase in delinquency due to payment that has not been paid. The passage of time causes both the risk and delinquency of the member to increase,attracting judicialization processes. It is important to emphasize that the cooperative must recognize and visit the homes of both the debtor member and his guarantor and also manage collection efforts. In the country´s economy,savings and credit coopertives are important for all citizens since they grant loans to various sectors to improve the lives of families, organizations and financial institutions, cooperatives arrive where there are fewer economic resources, they exist with accessibility fast concise and precise when offering the service. The analysis of this case study will allow to know the destinations of credit, collection processes and anticípate future late áyment and observe the position of the cooperative in the function of its admnistration has benn correct.